Ocorrência da infecção pelo vírus da imunodeficiência felina e da leucemia felina em gatos de Belo Horizonte, Minas Gerais - Bruno Marques Teixeira (2005)
The feline immunodeficiency vírus (FIV) is a lentivirus that causes immunodeficiency in domestic cats. The disease is characterized by a prograssive decline of the number of circulating CD4+ T cells, leaving the animals susceptible to opportunistic infections. In this work, we determined the ocorrency of the FeLV and FIV infection in a colony of free-roaming cats cached on the streets of Belo Horizonte - Minas Gerais - Brazil - and kept in confinement and its relationship with hematological abnormalities and clinical alterations. Additionally we compared two methods of detection of the disease (ELISA and PCR). One hundred forty five samples of peripheral blood mononuclear cells were amplified by PCR with synthetic promers, P24-1 and P-24-2 corresponding to the fragment of gag proviral gene. Forty out the 145 samples collected were also tested in a commercial kit (ELISA - SNAP® Combo FeLV/FIV). The results have showed that the ocorrency of FIV in the studied colony was 4,14%, by PCR and the FeLV was 32,5%, by ELISA. Additionally our research pointed that only the weight loss in the clinical abnormalities parameters observations presented statistic positive relationship with FIV infectivity. We also found out that both methods present similar sensitivity and specificity.